2006
DOI: 10.3748/wjg.v12.i12.1821
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal manifestations in myotonic muscular dystrophy

Abstract: Myotonic dystrophy (MD) is characterized by myotonic phenomena and progressive muscular weakness. Involvement of the gastrointestinal tract is frequent and may occur at any level. The clinical manifestations have previously been attributed to motility disorders caused by smooth muscle damage, but histologic evidence of alterations has been scarce and conflicting. A neural factor has also been hypothesized. In the upper digestive tract, dysphagia, heartburn, regurgitation and dyspepsia are the most common compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(75 citation statements)
references
References 61 publications
1
71
0
2
Order By: Relevance
“…Researchers highlight that up to 40% of children and young adults can experience GI symptoms, which include pain, bloating, altered bowel habit, and constipation. 9 Furthermore, Rönnblom et al 10 conducted a study in 2002 to monitor gastric emptying in 10 patients with MD; in this study, they suggested that MD is associated with reduced gastric motility. However, because of a lack of high-quality studies, it is still up for debate whether MD causes CIPO via damage to the enteric nervous system, smooth muscle, or secondary endocrine changes.…”
Section: Figurementioning
confidence: 99%
“…Researchers highlight that up to 40% of children and young adults can experience GI symptoms, which include pain, bloating, altered bowel habit, and constipation. 9 Furthermore, Rönnblom et al 10 conducted a study in 2002 to monitor gastric emptying in 10 patients with MD; in this study, they suggested that MD is associated with reduced gastric motility. However, because of a lack of high-quality studies, it is still up for debate whether MD causes CIPO via damage to the enteric nervous system, smooth muscle, or secondary endocrine changes.…”
Section: Figurementioning
confidence: 99%
“…The percutaneous gastrostomy is quite regular, although there are also complications described during (re)placement. In myotonic dystrophy impairment of gastrointestinal motility is known and seems to be gradual worsening (Bellini et al 2006), probably related to gastrointestinal symptoms like regurgitation, dyspepsia, abodominal pain, bloating, and changes in bowl habits. Although there is only a low correlation between the degree of skeletal muscle involvement and the presence and severity of gastrointestinal disturbances it is a positive correlation (Bellini et al 2006).…”
Section: Gastrointestinal Problemsmentioning
confidence: 99%
“…In myotonic dystrophy impairment of gastrointestinal motility is known and seems to be gradual worsening (Bellini et al 2006), probably related to gastrointestinal symptoms like regurgitation, dyspepsia, abodominal pain, bloating, and changes in bowl habits. Although there is only a low correlation between the degree of skeletal muscle involvement and the presence and severity of gastrointestinal disturbances it is a positive correlation (Bellini et al 2006). Also in boys with Duchenne and Becker muscular dystrophy abnormalities in gastric motility are seen and the possibility of progressive failure in neuromuscular function is put forward (Borelli et al 2005).…”
Section: Gastrointestinal Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The gastrointestinal tract is often involved in patients with MD, and digestive symptoms may be the first sign of dystrophic disease and may precede the musculo-skeletal features (2).…”
Section: Introductionmentioning
confidence: 99%